Upfront payments and listing decisions - Pio Baake; Vanessa von Schlippenbach (Deutsches Institut für Wirtschaftsforschung (DIW), 2008)
We analyze the listing decisions of a retailer who may ask her suppliers to make upfront payments in order to be listed. We consider a sequential game with upfront payments being negotiated before short-term delivery contracts. We show that the retailer is more likely to use upfront payments the higher her bargaining power and the higher the number of potential suppliers. Upfront payments tend to lower the number of products offered by the retailer when the products are rather close substitutes. However, upfront payments can increase social welfare if they ameliorate inefficient listing decisions implied by short-term contracts only.
Keywords: L14; L42; 330; Buyer power; upfront payments; retailing; Sortiment; Einzelhandel; Verhandlungsmacht; Lieferanten-Kunden-Beziehung; Konsumgüterindustrie; Betriebliche Preispolitik; Wohlfahrtseffekt; Theorie